Analisis Indikasi Manajemen Laba pada Perusahaan yang Dikenai Suspensi Akibat Keterlambatan Publikasi Laporan Keuangan Tahunan - Kornelia Er Lines; Tri Joko Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine differences in earnings management between firms subject to trading suspension due to delayed financial reporting and firms that reported their financial statements on time. Earnings management is measured using the F-Score model. The study population consists of all firms listed on the Indonesia Stock Exchange during the 2021-2024 period. Using purposive sampling, 108 observations were obtained, including 33 from suspended firms and 75 from firms that reported on time. Hypothesis testing was conducted using the Mann-Whitney U test to compare the F-Score and its seven components: RSST accruals, change in receivables, change in inventory, soft assets, change in cash sales, change in return on assets (ROA), and securities issuance. The results of this study indicate that firms with delayed financial reporting exhibit a higher level of earnings management than firms that reported their financial statements on time. This difference is primarily reflected in higher values of change in cash sales and securities issuance, while no significant differences were found in RSST accruals, change in receivables, change in inventory, soft assets, or change in return on assets (ROA) between the two groups.